ISOTOPE FRACTIONATION BY NATURAL POPULATIONS OF SULFATE-REDUCING BACTERIA - Canfield D.E. (My University, 2001)
Isotope fractionation during sulfate reduction was explored for natural populations of sulfate-reducing bacteria. High fractionations of 30%% to 40%% were produced when the natural population metabolized with indigenous organic substrate at environmental temperatures of 15°C to 25°C. Fractionations were unaffected by changes in sulfate concentration between 2 mM and 28 mM. After the natural substrate was exhausted, the sulfate-reducing bacterial population metabolized, in turn, with acetate, ethanol, and lactate. The high fractionations encountered with natural substrate were only reproduced when the amended substrate was supplied at concentrations limiting the activity of the sulfate-reducing population. Higher, nonlimiting concentrations of amended substrate produced lower fractionations of 16%% to 21% at 25°C. The natural sulfate-reducing population, therefore, probably experienced substrate limitation while utilizing the natural substrate. At the low temperature of 5°C fractionations with amended substrate ranged from 8%% to 14%% and were lower than expected based on the normal relationship between rates of sulfate reduction and the extent of isotope fractionation. The processes likely acting to control the magnitude of isotope fractionation are discussed.